Case report: Idiopathic subglottic stenosis in a girl; successful treatment with macrolides - Tebbe, Wolfgang; Wittkowski, Helmut; Tebbe, Johannes; Hülskamp, Georg (Frontiers in Pediatrics, 2022)
An eight-year-old girl presented with treatment-refractory cough and inspiratory stridor. Bronchoscopies showed progressive scarring leading to narrowing of the proximal trachea (Myer-Cotton Grade 2) and epithelial metaplasia of the tracheal and bronchial mucosa. After excluding other causes of congenital and acquired tracheal stenosis an idiopathic subglottic tracheal stenosis (iSGS) was diagnosed. Because of the patient´s young age a judicious therapeutic approach seemed appropriate. Therapy with Azithromycin, followed by Roxithromycin, was started. Symptoms almost completely subsided, spirometry normalized, and endoscopic and histologic findings improved considerably. Therapy has been continued for over three years with normal lung function values, and no compromise on physical activities and development. In instances of iSGS, therapy with macrolides is worth considering before more invasive procedures such as dilatation, laser, intralesional injections and surgical resection are performed.